Comparison of Phenolic Content of Indonesian Bay Leaves (Syzygium polyanthum) Fresh Decoction And Herbal Tea - Rahmawati, Irma; Kaswati, Lilih (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
The Indonesian bay leaf (Syzygium polyanthum) are one of the traditional cooking spices used in several countries in Southeast Asia, and this spice gives a distinctive herbaceous aroma. Bay leaves are often used as a medicinal plant for generations by the community to reduce cholesterol, diabetes, hypertension, gastritis, and diarrhea. The purpose of this study was to compare the content of polyphenols in Indonesian bay leaf decoction and bay leaf tea. The total phenolic content was determined by Folin-Ciocalteu’s method. The test results showed that the highest polyphenol content was found in bay leaf tea at 19.19 mg/kg, and then bay leaf decoction at 6.36 mg/kg. Based on the statistical analysis, it was stated that there was a difference in the levels of polyphenols in each sample, meaning that there was a significant difference. The implications of this study can be to develop processing techniques for Indonesian bay leaf which contain the best polyphenols for public consumption.